Mengatasi Masalah-Masalah Psikososial Akibat Ketunanetraan pada Usia Dewasa - Didi Tarsidi (Jurnal Pendidikan dan Kebudayaan, 2012)
This research has been conducted based on various theories and research findings revealing that blindness occurring during adulthood cause more problems than that occurring earlier in life. The research has been done to find a rehabilitation counseling model that can be used to help blind adults to more effectively overcome psychosocial problems caused by their blindness so that they will be able to regain their independence and will be able to achieve meaningful life. The rehabilitation counseling Model has been developed through research using exploratory mixed methods research design. The construct of the model has been developed based on the data of case studies on six persons whose blindness occurred during adulthood and they have proved to be successful in their lives. The model has been validated with expert judgment and tried out using single-subject research design on two relatively newly blind clients.